NETosis is critical in patients with severe community-acquired pneumonia - Zhang, Yiming; Li, Yan; Sun, Na; Tang, Hanqi; Ye, Jun; Liu, Yang; He, Quan; Fu, Yangyang; Zhu, Huadong; Jiang, Chengyu; Xu, Jun (Frontiers in Immunology, 2022)
Pneumonia is the fourth leading cause of death globally, and the reason for the high mortality rate of patients with severe community-acquired pneumonia (SCAP) remains elusive. Corticosteroid treatment reduces mortality in adults with SCAP but can cause numerous adverse events. Therefore, novel therapeutic targets need to be explored and new adjunctive immune drugs are urgently required. We analyzed the transcriptome data of peripheral blood leukocytes from patients with SCAP and healthy controls from three perspectives: differentially expressed genes, predicted functions of differentially expressed long non-coding RNAs, and transcriptional read-through. We discovered that the NETosis pathway was top-ranked in patients with SCAP caused by diverse kinds of pathogens. This provides a potential therapeutic strategy for treating patients. Furthermore, we calculated the correlation between the expression of genes involved in NETosis and the ratio of arterial oxygen partial pressure to fractional inspired oxygen. We identified four novel potential therapeutic targets for NETosis in patients with SCAP, including H4C15, H3-5, DNASE1, and PRKCB. In addition, a higher occurrence of transcriptional read-through is associated with a worse outcome in patients with SCAP, which probably can explain the high mortality rate of patients with SCAP.